Impact of prophylactic platelet transfusions on bleeding events in patients with hematologic malignancies: a subgroup analysis of a randomized trial (CME). Issue 10 (14th April 2014) - Stanworth, Simon J.; Estcourt, Lise J.; Llewelyn, Charlotte A.; Murphy, Michael F.; Wood, Erica M.; TOPPS Study Investigators
<x xml:space="preserve">Abstract</x> Background A recent randomized trial compared a policy of no prophylaxis with a policy of prophylactic platelet (PLT) transfusions at counts of fewer than 10 × 109/L in patients with hematologic malignancies. The results suggested the effectiveness of prophylactic PLT transfusions may vary according to patient diagnosis and treatment plan. Study Design and Methods This article presents full subgroup analyses and compares treatment effects between autologous hematopoietic stem cell transplantation (autoHSCT; n = 421) and chemotherapy/allogeneic HSCT (chemo/alloHSCT; n = 179) patients. Results Prespecified subgroup analysis found that the reduction in proportion of patients experiencing WHO Grade 2 to 4 bleeds (main trial outcome) seen in the prophylaxis arm was of greater magnitude in chemo/alloHSCT than autoHSCT patients (interaction p = 0.04). Analysis of secondary outcomes showed a shorter time to first bleeding episode with no prophylaxis in the chemo/alloHSCT group (hazard ratio, 1.84; 95% confidence interval CI, 1.21‐2.79; p = 0.004) compared to the autoHSCT group (hazard ratio, 1.12; 95% CI, 0.85‐1.48; p = 0.4; interaction p = 0.08). The increased number of days with Grade 2 to 4 bleeds with a no‐prophylaxis policy was similar in chemo/alloHSCT (rate ratio, 1.89; 95% CI, 1.10‐3.26) and in autoHSCT patients (rate ratio, 1.43; 95% CI, 1.04‐1.97). Both subgroups showed significant reductions in PLT transfusions with a no‐prophylaxis strategy. Conclusion There is evidence that the effectiveness of prophylactic PLT transfusions may differ between subgroups, with chemo/alloHSCT patients receiving prophylactic PLT transfusions appearing to show a greater reduction in bleeding outcomes compared to patients following a no‐prophylaxis policy.